Association and Variation among Some Important Nutritional Traits of Kair (Capparis decidua) - Kumar, S; Ali, S; Saxena, S N; Mahla, H R; Sharma, T B; Sharma, R (Annals of Arid Zone, 2016)
The natural variability in contents of various metabolites and minerals in buds and fruits of kair (Capparis decidua) has been studied. The results showed that fruits and buds of kair are rich in carbohydrates, protein and calcium. The mean and variance of carbohydrates and moisture were not significantly different in fruits and buds. However, the variability was much higher for minerals like zinc and sodium in fruits and zinc and iron in buds. Various traits of fruits as well as buds were correlated either negatively or positively in wild populations of kair. This information can be used for selection of desired genotypes for domestication and preservation of diversity. Key words: Capparis, kair, biochemical analysis, mineral, variability, fruits, buds.